Fostering Islamic Character Through Parent-School Synergy in Education: Menumbuhkan Karakter Islami Melalui Sinergi Orang Tua-Sekolah dalam Pendidikan - Fahruddin , Fahruddin; Astutik, Anita Puji (Journal of Islamic and Muhammadiyah Studies, 2025)
General Background: Schools play a crucial role in shaping students' personalities, particularly in instilling Islamic values. Specific Background: The synergy between parents and schools is essential for fostering akhlakul karimah at SD Muhammadiyah 2 Tulangan. Knowledge Gap: There is limited research on the specific processes and impacts of this synergy in educational settings. Aims: This study aims to elucidate the implementation of parent-school synergy in building an Islamic culture and its effects on students' Islamic character. Results: Active parental participation significantly enhances the formation of Islamic character through mutual understanding, communication forums, and involvement in school activities. Novelty: The study presents a structured framework for collaboration, demonstrating its effectiveness in promoting integrated Islamic education. Implications: Strengthening parent-school partnerships is vital for achieving educational success in fostering strong Islamic values among students. Highlights: Parental Engagement: Active participation of parents enhances students' Islamic character development. Structured Framework: Implementation of communication forums and workshops fosters mutual understanding. Holistic Education: Collaboration between parents and schools promotes an integrated approach to Islamic education. Keywords: Synergy, Parental Involvement, Character Development, Education, Islamic Culture